Indonesian's Ship Safety Assessment Strategy - Faturachman, Danny; Shariman, Mustafa (2012)
Indonesia is the worldâs largest archipelago, 2/3 of the country is covered by sea. But due to many factors a lot of ship accidents occurred every year, and claiming a large number of casualties. Efforts have been done to improve the safety of domestic sea transportation, as the result to be fully compliance to the SOLAS regulations, worsen by the varying sea and cargo characteristics, and low educated passengers, they are very vulnerable to accidents. Research is being carried out to explore the most appropriate strategy for ensuring the safety of ship operating on Indonesian waters using various methods, where four most influencing aspects i.e. Software, Hardware, Environment, and Live-ware are put into considerations. The existing conditions and experience learned from the past, backgrounds and sources of accident/incident are investigated, based on the findings feasible strategy is proposed, which will include the design requirements; qualification of personnel, refined rules, and operational efficiency.